Transmission expansion programme for electric network reinforcement - Oluseyi, P. O.; Ajekigbe, T. O.; Akintunde, T. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Due to the increase in electricity demand, transmission sector has become overstressed since it can only be built at vast cost. In many developing economies, the network is highly susceptible to outages, collapse as well as partial or total failures, since the existing transmission capacity limit is often closely approached. To overcome this challenge better transmission expansion needs to be considered. This paper identified the implementation of transmission expansion with a number of creative approaches for overcoming network collapse in poor economy. The study deployed the application of improved Strength Pareto Evolution Algorithm (SPEA-2) optimization approach for solving the transmission expansion problem based on a simple power flow model. This model was deployed for running the Nigeria-31-bus system; to serve as the benchmark hence the standard IEEE 30-bus system was also considered. Using the traditional approach, the  results obtained from the power flow analysis revealed  that there are four major buses that recorded very high severity of violation. These were  Jos, Kaduna, Kano and Birnin-Kebbi buses. In furtherance to this,  additional effort was made to establish these findings by adapting the contingency analysis tests which provided more information on the earlier results so as to establish that these buses made the adjoining transmission lines connecting them to be identified as weak. Thus this serves as the contributory factor to the  violation experienced by the entire the power network. For a more creative vivid display of the results; the Powerworld software was engaged for the analysis of the existing Nigeria-31 bus system while the violated buses that require more energy flow were provided with double circuit. This, thus, resulted in improved power outflow and inflow to the buses which led to  the reduction of losses in the network. In conclusion,  this study established that the transmission line connecting the geographical northern and southern parts of Nigeria dissipated quantifiably large value of losses which is mainly due to the nature and length of the line linking the source of electricity supply to a number of the load centres in the farther part of the country. Hence, it is suggested that the transmission expansion programme should be adopted for the improvement of power flow quantity which will, on the long run, reduce  the power loss suffer by the existing network.